University Preparatory Popular Courses as affirmative action: potentialities in access to Higher Education - Campagni, Caroline Rocha [UNESP]; Fonseca, Debora Cristina [UNESP] (Univ Federal Santa Maria, 2024)
The history of (not)paths of Basic Education in Brazil excluded the poor from higher levels of education, and In this sense, the emergence of University Preparatory Popular Course comes as a form of affirmative action, which aims to help the marginalized population access the university. In this paper we present part of the results of a case study that seeks to discuss if and how the TRIU, a Pre -University Course in the countryside of Sao Paulo, expands the possibilities of students' access to Higher Education. This work is a qualitative research of an interpretative and critic nature and was guided by the concepts of Freire and Hooks. To obtain data we analyzed documents, applied questionnaires and conducted semi -structured interviews. All collected data was analyzed through Content Analysis (BARDIN, 2004). This research found that the pedagogy of affection, popular education, the reception practiced in the TRIU have an important role for there to be an effective learning of the contents, triggering the entry of its students in the Higher Education Institution.
Keywords: Affirmative action; University Preparatory Popular Course; Access policies